New Trends in Vibration Based Structural Health Monitoring - Deraemaeker, Arnaud; Worden, Keith; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
This book is a collection of articles covering the six lecture courses given at the CISM School on this topic in 2008. It features contributions by established international experts and offers a coherent and comprehensive overview of the state-of-the art research in the field, thus addressing both postgraduate students and researchers in aerospace, mechanical and civil engineering.
Keywords: Engineering; Vibration; Mechanical engineering; Astronautics; Civil engineering; Engineering; Mechanical Engineering; Aerospace Technology and Astronautics; Civil Engineering; Vibration, Dynamical Systems, Control